2006
DOI: 10.1080/10236240600688789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of invasive tagging on the activity ofHolothuria whitmaei[Echinodermata: Holothuroidea]: A suitable mark-recapture method for short-term field studies of holothurian behaviour

Abstract: Although mark-recapture techniques traditionally have been used to obtain ecological data, tagging of soft-bodied holothurians has proven difficult, and the degree to which invasive tags may confound the behaviour of holothurians remains unclear. In this study, diurnal patterns of activity were monitored in the commercial sea cucumber Holothuria whitmaei (black teatfish) after marking the tegument superficially with a number measuring 30 Â 20 mm (to a depth of 2 mm). Rates of activity in marked specimens incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Where it was not possible to locate specimens within the study area ( Fig. 1), individuals were translocated from adjacent areas of reef flat, but never from distances greater than 100 m. For identification, each animal was marked with a number (following the methods of Reichenbach, 1999;Mercier et al, 2000) and left to recover for at least 5 days; the period required for marked specimens to elicit rates of activity statis- tically equivalent to control specimens (Shiell, 2006). For ease of diver navigation, the boundaries of the study sites were connected with submerged string lines, and the position of animals indicated by coloured plastic tape attached to the nearest hard object.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where it was not possible to locate specimens within the study area ( Fig. 1), individuals were translocated from adjacent areas of reef flat, but never from distances greater than 100 m. For identification, each animal was marked with a number (following the methods of Reichenbach, 1999;Mercier et al, 2000) and left to recover for at least 5 days; the period required for marked specimens to elicit rates of activity statis- tically equivalent to control specimens (Shiell, 2006). For ease of diver navigation, the boundaries of the study sites were connected with submerged string lines, and the position of animals indicated by coloured plastic tape attached to the nearest hard object.…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 Results of the two-factor repeated measures ANOVA and pairwise post hoc procedures assessing the effect of time of day (T) and site (S) on the animal's distance from shelter during August, It is not clear why up to 23% of H. whitmaei specimens were hidden from some time during the night until midday. Monitoring of sheltering behaviour began 5 days following marking, so it is unlikely the behaviour resulted from stress associated with initial handling (Shiell, 2006). Given that observations of sheltering behaviour were limited to August, 2003, it is possible that the results were confounded by water temperature.…”
Section: Sheltering Behaviourmentioning
confidence: 98%
“…However, density estimates should be considered with care (specially in rocky bottoms) due to H. mammata's cryptic nature (Navarro, 2012) and low recapture probability caused by the low readability of the marks. Marking by scratching is a common method used in sea cucumber mark-recapture studies (Reichenbach, 1999;Mercier et al, 2000;Navarro et al, 2013bNavarro et al, , 2014Siegenthaler et al, 2015), being considered less invasive and more effective than other methods such as glued tags, colouring agents, PIT tags and T-bar tags (Conand, 1990;Kirshenbaum et al, 2006;Shiell, 2006;Purcell et al, 2008;Navarro et al, 2014). However, based on our experience with the low readability of scratched marks on H. mammata' integument (previously commented in Methodology section), we suggest the search of other tagging methods for this species.…”
Section: Discussionmentioning
confidence: 99%
“…The whole study area was searched during each period of exposure (between 2 hours before low tide and 1 hour after it) and all holothurians found were marked in situ by means of scratching a code on their dorsal side (Reichenbach, 1999;Mercier, Battaglene, & Hamel, 2000;Navarro, García-Sanz, Barrio, & Tuya, 2013b;Siegenthaler et al, 2015) and released them at the same spot where captured. Although stress caused by marking and handling could result in increased initial activity (Shiell, 2006), scratching is considered as less invasive than other tagging methods (Conand, 1990;Kirshenbaum, Feindel, & Chen, 2006;Navarro, García-Sanz, & Tuya, 2014;Purcell, Agudo, & Gossuin, 2008;Schiell, 2006) and does not result in major behavioural changes (Mercier et al, 2000). Relative position (see Siegenthaler et al (2015) for the methodology used), total length (by means of metric tape), time and type of substrate were recorded for each sea cucumber sampled.…”
Section: Experimental Designmentioning
confidence: 99%
“…Before the beginning of monitoring, adult specimens were collected by SCUBA and transferred to preselected sites within the study area (see Shiell & Knott 2008). Individual Holothuria whitmaei specimens were then marked with a number and left to recover for a minimum of 5 d following Shiell (2006). Marker plates were placed directly posterior to each animal, from which point all subsequent movement was determined (following Mercier et al 2000, Uthicke 2001a).…”
Section: Methodsmentioning
confidence: 99%